Formulation of justifiable wind loading distributions up tall buildings derived from HFFB measurements - Salehinejad, M. Mahdi; Li, Yin Fai; Ma, Quincy; Flay, Richard George James (Engineering structures, 2024)
For the general case of non-linear and combined sway and twist mode shapes, analysis of HFFB measurements gives rise to serious challenges and various techniques have been developed using significant assumptions. This is because it is not possible to directly obtain the distribution of varying fluctuating wind loads throughout the height of tall buildings. This paper proposes a straightforward HFFB-based wind load/twist distribution approach in the time domain to predict the wind-induced dynamic response of tall buildings. Using this framework, it is possible to overcome the deficiencies of mode shape correction factor approach, and the complexity and impracticality of alternative approaches for tall buildings. Two 1:300 scale rigid models of benchmark tall buildings, IAWE Buildings A and B, have been selected to perform a detailed wind tunnel investigation as subjects to evaluate this proposed HFFB approach study. Building A has complex 3D mode shapes combining sway and twist, whereas the simpler Building B has uncoupled linear mode shapes in sway and twist. The high frequency pressure integration (HFPI) wind tunnel technique was utilised to measure surface pressure information in separate tests to obtain the reference wind loading for validation of the HFFB predictions. Furthermore, a commonly used HFFB mode shape correction factor approach was used to estimate the dynamic wind responses which were compared to those from the proposed approach. From the comparison between the aerodynamic and dynamic wind results from proposed HFFB approach and reference HFPI results, it is found that the proposed HFFB approach can predict the vertical distributions of the wind forces and torque (wind loads) with acceptable accuracy for carrying out the conceptual stage of tall building design. •A straightforward HFFB-based approach to estimate the time varying aerodynamic wind load/twist distribution over the height of tall buildings is described.•The output of this approach can be applied directly to a detailed structural finite element analysis model to determine wind responses without requiring any assumptions concerning mode shapes.•The proposed HFFB approach can be used to predict wind-induced dynamic response of any tall building with any mode shapes.•This approach was applied to two different buildings and its predictions agree well with reference HFPI predictions, and give more accurate predictions than the established HFFB mode shape correction factor approach.•The proposed approach approximates the wind loading distributions up the height of the building using two functions that always match the instantaneous base forces and moments, as well as a height varying torsional load.